Fe-doped CoP nanosheet arrays: an efficient bifunctional catalyst for zinc–air batteries. Issue 55 (26th June 2018) - Qin, Xin; Wang, Zao; Han, Jingrui; Luo, Yonglan; Xie, Fengyu; Cui, Guangwei; Guo, Xiaodong; Sun, Xuping
Abstract : Fe-doped CoP nanoarrays on nickel foam (Fe0.33 –CoP/NF) act as a superior bifunctional electrocatalyst to CoP/NF for both the OER and ORR in alkaline media. In concentrated alkaline media, zinc–air batteries based on Fe0.33 –CoP/NF exhibit a power density of 63 mW cm −2 with a long cycle life (up to 200 h). Abstract : It is highly desired to design and develop low-cost and efficient bifunctional electrocatalysts for zinc–air batteries (ZABs). In this communication, we report that Fe-doped CoP nanosheet arrays on nickel foam (Fe0.33 –CoP/NF) act as a highly active bifunctional electrocatalyst for both the oxygen reduction reaction and the oxygen evolution reaction in alkaline media. We further demonstrate the use of Fe0.33 –CoP/NF as the cathode to construct rechargeable ZABs with superior performance to that of the CoP/NF counterpart. In concentrated alkaline electrolytes, such ZABs exhibit a higher power density of 63 mW cm −2 than that of CoP/NF (23 mW cm −2 ) with a long cycle life (up to 200 h).